Global Talent Flows - Sari Pekkala; William Kerr; Caglar Ozden; Christopher Parsons (Institute for the Study of Labor (IZA), 2016)
The global distribution of talent is highly skewed and the resources available to countries to develop and utilize their best and brightest vary substantially. The migration of skilled workers across countries tilts the deck even further. Using newly available data, we first review the landscape of global talent mobility, which is both asymmetric and rising in importance. We next consider the determinants of global talent flows at the individual and firm levels and sketch some important implications. Third, we review the national gatekeepers for skilled migration and broad differences in approaches used to select migrants for admission. Looking forward, the capacity of people, firms, and countries to successfully navigate this tangled web of global talent will be critical to their success.
Keywords: F15; F22; J15; J31; J44; L14; L26; O31; O32; O33; 330; migration; talent; diaspora